Electrical Conducting Properties of LSF-Based Composites as an Interconnection of Tubular Type of Solid Oxide Fuel Cells. (2nd June 2015) - Yu, Ji Haeng; Lee, Hee Lak; Shin, Hyung Chul; Cho, Sangyoung; Joo, Jong Hoon; Yoo, Chung-Yul
Abstract : We investigated La0.8 Sr0.2 FeO3 -δ (LSF)-based composite materials as the interconnection for tubular SOFCs. LSF is a mixed ionic and electronic (hole) conducting material and thus shows low electrical conductivity in reducing (H2 ) atmosphere. However, composite materials with LSF and ceria show moderate electrical conductivity by electronic leakage current through doped ceria and LSF. LSF-GDC composite and LSF layers were successfully deposited on NiO-YSZ anode substrate by conventional co-firing process. The area specific resistance of LSF/LSF-GDC bilayer on Ni-YSZ measured in air//H2 condition was initially ~50 mΩcm 2 .